Fortilin binds IRE1α and prevents ER stress from signaling apoptotic cell death - Pinkaew, Decha; Chattopadhyay, Abhijnan; King, Matthew D.; Chunhacha, Preedakorn; Liu, Zhihe; Stevenson, Heather L.; Chen, Yanjie; Sinthujaroen, Patuma; McDougal, Owen M.; Fujise, Ken (Nature communications, 2017)
The endoplasmic reticulum, the cytoplasmic organelle that matures a massive amount of nascent secretory polypeptides, is particularly sensitive to stress. Endoplasmic reticulum stress causes unfolded proteins to populate the organelle, eliciting the unfolded protein response. During the unfolded protein response, GRP78—an endoplasmic reticulum master stress regulator—detaches from three endoplasmic reticulum stress sensors (IRE1α, PERK, and ATF6) and allows them to activate the apoptotic signaling pathway. Fortilin, a pro-survival molecule, is known to inhibit apoptosis by binding and inhibiting p53, but its role in endoplasmic reticulum stress-induced apoptosis remains unknown. Here, we report that fortilin directly interacts with the cytoplasmic domain of IRE1α, inhibits both kinase and endoribonuclease (RNase) activities of the stress sensor, and protects cells against apoptotic cell death at both cellular and whole animal levels. Our data support a role of fortilin in the unfolded protein response and its potential participation in human diseases caused by unfolded protein response. IRE1α is an ER stress sensor, whose activity induces apoptosis. Here, the authors report that fortilin, a pro-survival factor, with yet unknown roles in ER stress, interacts with active IRE1α, inhibits both its kinase end RNase activities, and protects cells from apoptosis both in vitro and in vivo.